Motivational profiles of kindergarten teachers in minority areas of China and their association with outcomes - Shi, Dasheng; Zhang, Mengmeng; Chen, Ye; Jin, Ruining; Yang, Xiantong (Frontiers in Psychology, 2022)
Academic discourses regarding teacher motivation have been on-going for decades for those who teach in ethnic minority areas. Yet research findings failed to provide a consistent conclusion regarding if kindergarten teachers’ motivation pattern would vary based on a case-to-case scenario. Therefore, further studies are needed to probe the motivation patterns among this population. The study firstly examined kindergarten teachers’ motivational profiles based on Expectancy Value Theory (EVT), and then examined how teachers’ motivation related to outcome variables (work engagement, workplace wellbeing, and retention intention). Participants included 1,199 kindergarten teachers from ethnic minority areas in China. Latent profile analysis identified three motivation profiles for teachers: low value-high cost (profile 1), moderate all (profile 2), and high value-low cost (profile 3). Teacher with different motivation profiles had significant differences in work engagement, workplace wellbeing, and retention intention. In addition, chain mediation analysis revealed that work engagement and workplace wellbeing mediated the relationship between motivation profiles and retention intention. The implications of the findings for study are discussed.